2020
DOI: 10.1002/hed.26380
|View full text |Cite
|
Sign up to set email alerts
|

Primary tumor volume as a predictor of distant metastases and survival in patients with sinonasal mucosal melanoma

Abstract: Background: Sinonasal mucosal melanoma (SNMM) is an aggressive cancer with high mortality. Identifying patients at risk of distant metastasis assists with management and prognostication. We aimed to define the relationship between volume, survival, and risk of distant metastases. Methods: A retrospective review of all patients with SNMM treated at a single institution over a 21-year period was conducted. Tumor volume was calculated using cross-sectional imaging and survival analysis was performed. Results: Six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…MMHN is an aggressive malignancy whose comprehensive treatment modalities are complex and clinical outcomes are still unsatisfactory 12 . The AJCC 8th edition staging system lacks the ability to predict prognosis 13 . MMHN patients in the same stage can have obviously different survival rates 14 .…”
Section: Discussionmentioning
confidence: 99%
“…MMHN is an aggressive malignancy whose comprehensive treatment modalities are complex and clinical outcomes are still unsatisfactory 12 . The AJCC 8th edition staging system lacks the ability to predict prognosis 13 . MMHN patients in the same stage can have obviously different survival rates 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Researches on other tumors also support this conclusion. GTV_P volume ≥5 cm 3 was associated with a significantly worse OS in patients with sinonasal mucosal melanoma [ 33 ]. Another finding suggested that a pathological tumor volume of ≥18 cm 3 was significantly correlated with shorter OS of oral squamous cell carcinoma [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The remarkable rate of distant metastasis regardless of the stage at presentation [4,142] makes MM similar to a systemic tumor, leading several authors to conclude that systemic therapy should be part of the future standard of care even in the curative setting [143]. Since tumor volume has been demonstrated to predict the risk of distant metastases and death, then it could be employed as a TDTC to implement systemic therapy in initial treatment [141,144]. Currently, chemotherapy has a limited role in the management of MM, especially in the curative setting [145].…”
Section: Mucosal Melanomamentioning
confidence: 99%